2020
DOI: 10.1111/imj.14732
|View full text |Cite
|
Sign up to set email alerts
|

Who is asking about medicinal cannabis in palliative care?

Abstract: Following legislative changes in the availability and prescribing of medicinal cannabis in Australia, we sought to understand prospectively the nature of information seeking and requests for medicinal cannabis in consultations between palliative care clinicians and patients with cancer. The 104 discussions were overwhelmingly initiated by patients and carers (93%) and were for a variety of symptoms, reflecting high levels of patient interest in the use of medicinal cannabis in cancer. AbstractPsittacosis is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Interest in medicinal cannabis is high [ 26 ], driven by strong public interest and word of mouth [ 35 ]. It is noteworthy that few interviewees in this study described seeking or receiving information about medicinal cannabis from a health care professional, instead more often opting to obtain information and opinions from popular media, family, and friends.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interest in medicinal cannabis is high [ 26 ], driven by strong public interest and word of mouth [ 35 ]. It is noteworthy that few interviewees in this study described seeking or receiving information about medicinal cannabis from a health care professional, instead more often opting to obtain information and opinions from popular media, family, and friends.…”
Section: Discussionmentioning
confidence: 99%
“…As such, suggestions within the RCT recruitment literature that focus on increasing awareness of the health problem and of the benefits of the intervention [ 7 , 9 ] are to some degree already attended to within the context of RCTs of medicinal cannabis in advanced cancer care settings—patients have a high level of awareness of the intervention. Health professionals, however, need a stronger evidence base to guide patients with confidence [ 26 ], and this warrants further RCTs into medicinal cannabis in palliative and other care settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was evident in the present study where consumer participants suggested they understood medicinal cannabis may be a treatment of cancer itself. This view was also held by 25% of patients requesting medicinal cannabis in outpatient clinics 19 . To address this misunderstanding directly, the developed resource states that medicinal cannabis is not a cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…stated that they believed it was efficacious or were using it in part for cancer treatment, 243,244 with further studies reporting patient discussions regarding this intent. 245,246 This disparate belief in efficacy is in part driven by patient access to curative claims made on the internet where patient testimonials and anecdotal evidence appears to support such claims. 247 Published case reports provide legitimacy, 248,249 while there are a lack of randomised controlled trials against which doctors can form evidence-based decisions.…”
Section: -106mentioning
confidence: 99%